Feasibility of Independent Oriented Learning Devices Independent Campus Learning (ICL) Study Program (SP) Diploma 3 (D3) Mechanical Engineering Bali State Polytechnic - Ketut Darma, I; Wayan Suastawa, I; Putu Darmawa, I (KnE Social Sciences, 2024)
The Independent Campus Learning (ICL) Policy is one of the policy studies the government is currently promoting to implement in universities. Implementing this policy in educational programs requires readiness in the study program. Having appropriate learning tools demonstrates this readiness and adherence to the ICL curriculum. In adherence to this policy, the D3 Engineering Study Program (SP) at Bali State Polytechnic (BSP) developed learning tools aligned with the ICL Curriculum. The objective of this study is to assess the feasibility of learning materials, including Semester Learning Plans (SLP) and textbooks oriented to the ICL curriculum in the D3 Mechanical Engineering study program. The developers employed a research and development approach, utilizing the Borg & Gall model modified into three development stages: preliminary studies, product design, and development and evaluation. The assessment of experts is used to review the feasibility aspect. The feasibility test involved three experts: content, media, and practitioners. Results indicate that the feasibility of Semester Learning Plans (SLP) and textbooks reached 87.5%, with 84.6% categorized as very feasible and appropriate. The Semester Learning Plans (SLP) and textbooks are straightforward and suitable for implementing the ICL curriculum in the BSP’s D3 Mechanical Engineering study program. Nonetheless, minor revisions are required. The implication is that after revision, Prototype I can proceed to the next development stage, involving practicality and testing product effectiveness. Keywords: independent campus learning, curriculum, learning devices, feasibility